Magnetic Properties of Vanadium(Iv)-Based Extended Systems: [(Vo) 3(?-Po4)2(2,2?-Bpy)(?-Oh 2)]·1/3h2o and (Vo)2h4p 2o9 - Venegas-Yazigi, D; Venegas-Yazigi, D; Muñoz-Becerra, K; Muñoz-Becerra, K (2013)
The magnetic properties of [(VO)3(?-PO4) 2(2,2?-bpy)(?-OH2)]1/3H2O (1) and (VO)2H4P2O9 (2), a tubular and a layered vanadium(IV) phosphates containing triply oxido bridged VIV dimers, are analyzed considering the Bleaney-Bowers S = 1/2 dimer model. In compound 1 the presence of an additional VIV connected with the VIV dimers through ?1,2-PO4 3- bridges is described with a Curie-Weiss type correction. This model reproduces the magnetic properties of compound 1 with g = 1.956, Jdim = -102.1 cm-1, ? = -0.4 cm-1 and N? = 278 × 10-6 emu mol-1. In compound 2, the presence of a small percentage of paramagnetic impurity has to be considered to account for the divergence of ?m at low temperatures. This simple model reproduces the magnetic data of compound 2 with g = 1.99, J = -62.4 cm -1 and a 1.2% of monomeric impurity. The moderate antiferromagnetic coupling found in the triply oxido bridges VIV dimers is justified from the structural parameters of the bridge. These studies confirm that the coupling through -O-P-O- bridges is antiferromagnetic and relatively weak, as well as previous magneto-structural correlations in this kind of oxido bridges. DFT calculations on a dinuclear fragment model for the two systems gave the following values of Jcalc = -72.4 cm-1 for 1 and J calc = -5.2 cm-1 for 2. These values reproduce the antiferromagnetic nature of the superexchange interactions between the V IV centers. © 2012 Elsevier B.V. All rights reserved.
Keywords: VPO; Hybrid materials; Molecular magnetism; Vanadium; DFT